2022
DOI: 10.1101/2022.10.20.513023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing Eastern spruce budworm’s large-scale dispersal events through flight behavior and stable isotope analyses

Abstract: Eastern spruce budworm moth (Choristoneura fumiferana(Clem.)) mass outbreaks have widespread economic and ecological consequences. A key explanation for the large-scale spread and synchronization of these outbreaks is the long-distance dispersal (up to 450km) of moths from hotspots (high-density populations) to lower-density areas. These events have proved difficult to monitor because dispersal flights occur only a few times a year, have no consistent routes, and commonly used tracking methods (e.g., populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Strontium isotope ratios have already been applied to the geographic assignment of monarch butterflies and other lepidopteran species and showed great promise for increasing the precision of isotope-based geographic assignment (Reich et al 2021, Dargent et al 2022. Here, we confirmed the assumption that the ⁸⁷Sr/⁸⁶Sr of monarch wings remain the same over time and continue to represent the larval signature despite adult feeding, at least in males (Figure 3B).…”
Section: Geolocation Using Metals and Metal Isotopessupporting
confidence: 81%
See 1 more Smart Citation
“…Strontium isotope ratios have already been applied to the geographic assignment of monarch butterflies and other lepidopteran species and showed great promise for increasing the precision of isotope-based geographic assignment (Reich et al 2021, Dargent et al 2022. Here, we confirmed the assumption that the ⁸⁷Sr/⁸⁶Sr of monarch wings remain the same over time and continue to represent the larval signature despite adult feeding, at least in males (Figure 3B).…”
Section: Geolocation Using Metals and Metal Isotopessupporting
confidence: 81%
“…Strontium isotope ratios have already been applied to the geographic assignment of monarch butterflies and other lepidopteran species and showed great promise for increasing the precision of isotope-based geographic assignment (Reich et al . 2021, Dargent et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The isoscape would also be applicable to trace the one-way dispersal and population connectivity of invasive insect pests. 9 The average uncertainty (17.3‰) obtained from the calibrated δ 2 H wing isoscape is higher than previous δ 2). The Brattström et al 29 Considering the scarcity of Mediterranean samples in Brattström et al, 29 the different transfer functions are not totally surprising as simulation exercises performed by Contina et al 40 showed that lack of sampling of isotope extremes of the range could lead to large difference in calibration lines.…”
Section: Multivariate Linear Mixed Model Predicting δ 2 H Wing Valuesmentioning
confidence: 66%
“…Hydrogen isotope composition (referred to subsequently as δ 2 H 8 ) is a promising tool to trace insect mobility and has been applied to a few insect species to study specific dispersal events, [9][10][11][12][13] single generations within the migratory cycle [14][15][16][17][18] and more rarely multigenerational migration. [19][20][21] The basis behind this approach is that the δ 2 H in water varies spatiotemporally and predictably on the landscape with temperature, elevation and continentality.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, many sources of variability in metal composition need to be further explored, including the effects of host plant (Bowden et al, 1984), microbial communities (Consuegra et al, 2020), parasitism (Sures, 2004), type of metamorphosis and life-stage, reproductive status, homeostatic mechanisms, and their interactions (Tibbett et al, 2021). Strontium isotope ratios have already been applied to the geographic assignment of monarch butterflies and other lepidopteran species and showed great promise for increasing the precision of isotope-based geographic assignment (Reich et al, 2021;Dargent et al, 2022). Here, we confirmed the assumption that the 87 Sr/ 86 Sr of monarch wings remain the same over time and continue to represent the larval signature despite adult feeding, at least in males (Figure 4B).…”
Section: Geolocation Using Metals and Metal Isotopesmentioning
confidence: 99%